Souvenir [videorecording (DVD)] - Defurne, Bavo, 1971-; Huppert, Isabelle; Azaïs, Kévin, 1992-; Leysen, Johan (Strand Releasing, 2018)
A forgotten European song contest singer, fading away in a pate factory, falls in love with a young aspiring boxer. Together they decide to attempt her comeback.